2010
DOI: 10.1093/hmg/ddq386
|View full text |Cite
|
Sign up to set email alerts
|

Functional relevance of the IRF-1 promoter polymorphism rs2549009 on transcriptional activity in a native genomic environment

Abstract: Interferon regulatory factor-1 (IRF-1), a transcription regulator involved both in inducing and in mediating the effects of interferon, is encoded by a highly polymorphic gene in different ethnic populations. Some of these genetic variations have been described to be associated to disease traits in hepatitis C virus and in human immunodeficiency virus infection, including one single-nucleotide polymorphism rs2549009 within the promoter region. This study aimed at investigating the functional relevance of rs254… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…C is -regulatory allelic effects may arise from allele-specific differences in transcription factor binding and enhancer activity (Agueda et al 2011; Bickel et al 2011; Colombo et al 2011; Harmon et al 2010; Mertens et al 2010). Transcription factor binding to a regulatory DNA element usually results in repositioning of nucleosomes.…”
Section: Resultsmentioning
confidence: 99%
“…C is -regulatory allelic effects may arise from allele-specific differences in transcription factor binding and enhancer activity (Agueda et al 2011; Bickel et al 2011; Colombo et al 2011; Harmon et al 2010; Mertens et al 2010). Transcription factor binding to a regulatory DNA element usually results in repositioning of nucleosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Peripheral blood monocytes (PBMCs) from approximately 30 ml of heparinized peripheral blood were isolated through Ficoll density gradient centrifugation according to standard procedures described previously [33]. Cell preparations were routinely assessed for viability (>95%) by trypan blue dye exclusion.…”
Section: Methodsmentioning
confidence: 99%
“…Linear regression analysis of data derived from the two different read out assays revealed a close correlation with p = 0.003 and r = 0.71. These results provide first evidence for a bidirectional IRF-1 gene expression imbalance in PBMC (ASTQ experiments were performed by our research team members; Mertens et al, 2010).…”
Section: Correlation Between Allele-specific Irf-1 Rs2549009 Promoter...mentioning
confidence: 65%
“…A parallel analysis of total IRF-1 gene expression revealed that total IRF-1 gene expression was not significantly different when related to IRF-1 rs2549009 promoter genotypes (p = 0.2709) in 41 healthy Caucasians. A more detailed analysis within the group of 16 individuals heterozygous in IRF-1 rs2549009, however, revealed a close and positive relation (p = 0.0035, r = -0.68) between the relative amount of G allele transcripts and total IRF-1 mRNA levels in PBMC (these analyses were done in cooperation with our research team members; Mertens et al, 2010).…”
Section: Further Functional Studies On Irf-1 Rs2549009 Gene Expressionmentioning
confidence: 97%
See 1 more Smart Citation